Zur Stellung der „mosaischen” Juden nach Bonhoeffers erster Judenschutzschrift „Die Kirche vor der Judenfrage” (1933) - Krumwiede, Hans-Walter (Kirchliche Zeitgeschichte, 2004)
Over the past sixty years, Bonhoeffer's reputation has risen steadily in ecumenical circles. But we should not forget that an early controversy arose amongst German Protestants as to the interpretation of his martyrdom. There were many, such as Bishop Meiser of Munich, who held that Bonhoeffer had been put to death as a political traitor, not as a Christian martyr. So too, there were those who argued that Bonhoeffer's sympathies had been engaged solely for the converted Jews, not for the whole Jewish population in general. In this particular article „The Church and the Jewish Question", he is alleged to have followed Luther's teaching in launching sharp attacks against the Jews, who were placed under a curse for their crime of putting Jesus to death, and who had so wantonly refused to be converted because of their horrendous obstinacy. Many people in the United States, including Jews, have stressed that it would be of incalculable benefit if this accusation against Bonhoeffer could be remedied, so that all Jews could be included in his sympathies. It now turns out that this so-called condemnation of Jews by Christians was incorrectly included as a Bonhoeffer quotation (G. Menken). The result, in my opinion, is that the road is now open for a genuine and respectful meeting between Israel and Christianity: The Christians will remain Christians and the Jews remain Jews. Both carry the burden of their biblical existence, which can lead to the fulfillment of the divine promises „when the hour comes".